Potent fluoro-oligosaccharide probes of adhesion in Toxoplasmosis. - Allman, SA; Jensen, H; Vijayakrishnan, B; Garnett, J; Leon, E; Liu, Y; Anthony, D; Sibson, N; Feizi, T; Matthews, S; Davis, B (2009)
Unnatural, NMR- and MRI-active fluorinated sugar probes, designed and synthesised to bind to the pathogenic protein TgMIC1 from Toxoplasma gondii, were found to display binding potency equal to and above that of the natural ligand. Dissection of the binding mechanism and modes, including the first X-ray crystal structures of a fluoro-oligosaccharide bound to a lectin, demonstrate that it is possible to create effective fluorinated probe ligands for the study of, and perhaps intervention in, sugar-protein binding events.